Health-Promoting Behaviors, Risk Perceptions, and Attention to COVID-19-Related Information: Comparing People's Responses to the COVID-19 Pandemic Across Times of Chinese New Year and Summer 2020 in Hong Kong - Xu, Yue; Chen, Hui-Fang; Yeung, Wai Keung Jerf; Hsieh, Chih-Wei; Yuan, Hsiang-Yu; Chang, Lennon Yao-Chung (Frontiers in Public Health, 2021)
Background: Since the start of the COVID-19 pandemic, individuals have been encouraged to engage in health-promoting behaviors, namely actions taken to prevent infection and keep themselves healthy, such as maintaining social distancing. However, other factors, such as risk perception and feelings of fear, also might influence whether an individual takes such measures. This study compared people's responses to the pandemic in terms of their adoption of COVID-19 health-promoting behaviors, COVID-19 risk perceptions, and attention to COVID-19-related information during two periods: the 2020 Chinese New Year (CNY) in Hong Kong (HK), i.e., the very beginning of the COVID-19 outbreak (Time 1, T1), and summer 2020, i.e., before and during the third wave of COVID-19 infections in HK (Time 2, T2). Methods: Data were extracted from 180 HK participants, who were asked to recall and report their health-promoting behaviors, emotional and cognitive COVID-19 risk perceptions, and attention to COVID-19-related information during T1 and T2. A repeated-measures ANOVA series was conducted to investigate differences in public responses between the two aforementioned time points. Main Findings: After controlling for the effects from gender, age, and education levels, the participants reported practicing more infection-prevention behaviors, experiencing a lower level of fear as a psychological response, and paying less attention to COVID-19-related information during T2 than T1. Conclusions: This study addressed the need to monitor public responses to the COVID-19 pandemic, including changes in people's behaviors and psychological responses across time. The results also suggest that the HK public was steered toward striking a balance between strengthening their infection-prevention behaviors and reducing their fear of COVID-19 infection.